2011
DOI: 10.1017/s0022278x11000024
|View full text |Cite
|
Sign up to set email alerts
|

Paying ‘buckets of blood’ for the land: moral debates over economy, war and state in Southern Sudan

Abstract: This paper challenges the prevailing focus on ethnic division and conflict in Southern Sudan in recent years, demonstrating that even within ethnically divisive debates over land, there are shared, transethnic levels of moral concern. These concerns centre on the commodification and monetisation of rural and kinship resources, including human life itself, epitomised in ideas of land being bought with blood, or blood being turned into money by the recent wartime economy. It argues that the enduring popular ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…This may deepen the dispossession derived from displacement. As people are not on the ground to stake their claims, and the state does not protect their rights, their lands get claimed by international or domestic actors [14,39]. In various settings in our research, we observed how widows, divorced women, and orphans notably fell victim to irregular appropriation of land after conflict.…”
Section: Unfavourable Conditions For Land Governancementioning
confidence: 85%
See 1 more Smart Citation
“…This may deepen the dispossession derived from displacement. As people are not on the ground to stake their claims, and the state does not protect their rights, their lands get claimed by international or domestic actors [14,39]. In various settings in our research, we observed how widows, divorced women, and orphans notably fell victim to irregular appropriation of land after conflict.…”
Section: Unfavourable Conditions For Land Governancementioning
confidence: 85%
“…Competing claims on the ground reflect these broader tensions and have political connotations far beyond individual concerns with livelihood security. This is clear in South Sudan, for example, where soldiers from the liberation movement SPLA, many of whom were Dinka from other parts of South Sudan, defended their occupation of lands and houses of people who had fled, arguing that they had 'liberated' these lands, spending their blood, while original residents had 'forfeited' their rights by fleeing [38,39]. As displaced people returned, however, seeking to recover their rights, they did not accept that these soldiers were victims but resented them as the vanguard of a Dinka agenda to (re-) occupy the southern part of South Sudan [22].…”
Section: Unfavourable Conditions For Land Governancementioning
confidence: 99%
“…During the 1983-2005 civil war, for instance, the SPLM leadership appointed chiefs to head ethnic groups or clans in areas it controlled, indoctrinated those groups in liberation ideologies, and used the groups to conscript soldiers and secure food for its fighting forces (Johnson 1998;Leonardi 2011). After independence, SPLM retained most chiefs it appointed during wartime, included them on the government payroll, and made them upwardly accountable to local government officials who are predominantly from the party.…”
Section: Identity As a Political Toolmentioning
confidence: 99%
“…These conflicts are reflected in conflicts over land distribution, where the Dinka in many places have settled on land claimed by returning refugees -this is particularly evident in Equatoria. 57 The Juba Declaration on Unity and Integration between the SPLM and the South Sudan Defence Forces (SSDF) was an important step to reconcile some of the conflicts in the south. 58 By this declaration, the SSDF, a collection of militias which had been allied with Khartoum government forces during the civil war, was integrated into the Southern Sudanese Army.…”
Section: Implementation Outputs and Perceptions Of The Cpamentioning
confidence: 99%